A special issue on Material Science based on the papers presented during Second International Conference on Material Science. (2018) - Arshad Hussain, Syed; Bhattacharjee, D.
Abstract: This special issue on different aspects of Material Science is based on the papers presented during Second International Conference on Material Science held at Department of Physics, Tripura University, India. The contributors to this special issue are from early carrier researchers to experts in their relative areas. Topics of the papers ranges between all the 13 sub themes of the conference. Out of total 211 presented papers 47 papers have been selected for this special issue after peer review.